INFLATION IN THE G7: MIND THE GAP(S)?. (19th December 2013) - Morley, James; Piger, Jeremy; Rasche, Robert; Kim, Chang-Jin; Morley, James; Piger, Jeremy
<x content-type="archive" xml:space="preserve">Abstract</x> We investigate the importance of trend inflation and the real-activity gap in explaining inflation in G7 countries since 1960. Our analysis is based on a bivariate unobserved components model of inflation and unemployment in which inflation is decomposed into a stochastic trend and a transitory component. As in recent implementations of the New Keynesian Phillips Curve, it is the transitory component of inflation, or "inflation gap, " that is driven by the real-activity gap, which we measure as the deviation of unemployment from its natural rate. We find that both trend inflation and the inflation gap have been consistent and substantial determinants of inflation at business cycle horizons for all G7 countries since 1960. Also, the real-activity gap explains a large fraction of the variation in the inflation gap for each country. These results provide empirical support for the New Keynesian Phillips Curve augmented with trend inflation.